There once was a world : a nine-hundred-year chronicle of the shtetl of Eishyshok - Eliach, Yaffa (Little, Brown, 1998)
The stories behind the 1,600 photographs on the shtetl of Eishyshok in the United States Holocaust Memorial Museum.